Pengaruh Kaidah Nahwu dalam Istinbath Hukum - Endri Yenti; Beni Firdaus; Rahmiati Rahmiati; Muhammad Afif Al fikri (Jurnal Kajian dan Pengembangan Umat, 2022)
That the differences of opinion in maintaining the rules of nahwu influence the legal product that is produced , the rules of nahwu is about the problems of i’rab and al-ma’ani letters . This research is in the form of library research, literature study can be interpreted as a data collection technique by conducting a study study of books, literatures,notes, and reports that have to do with the problem being solved which causes the different opinion of mufti againts it is: First: the different flow of nahwu knowledge which is influenced by Arabic with nonArabic because of spresding Islam that finally there is an effort arranging of nahwiyyah rules which is influenced by the characters where the rules are formed. Second, there are differences of qira’ah caused by several things, that are: the differences of Prophet’s qira’ah in conveying and teaching the Qur’an, there is Prophet’s taqrir against the various qira’ahprevailing among the muslims at that time, the difference of qira’ah caused by the difference of qira’ah that Allah SWT revealed to the Prophet, the difference qira’ah caused by the history of the companions of the Prophet SAW regarding the various versions of qira’ah that exists, the difference dialect of language among the Arabs at that time of the decline of the Qur’an, third, Qira’ah syazzah; some mufti differ in understanding the letters of al-ma’ani because some of them hold on to qiraa’ah syazzah, fourth: the differences in understanding the letters of al-ma’ani caused by the transfer of one meaning letter to another meaning because of the closeness of meaning.